2007
DOI: 10.1677/erc-07-0154
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin triggers senescence in K-ras transformed cells via RhoA-dependent downregulation of cyclin D1

Abstract: Arginine vasopressin (AVP), a vasoactive peptide hormone that binds to three G-protein coupled receptors (V 1 R, V 2 R, and V 3 R), has long been known to activate V 1 R and elicit mitogenesis in several cell types, including adrenal glomerulosa cells. However, in the mouse Y1 adrenocortical malignant cell line, AVP triggers not only a canonical mitogenic response but also novel RhoA-GTP-dependent mechanisms which downregulate cyclin D1, irreversibly inhibiting K-ras oncogene-driven proliferation. In Y1 cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
11
0
2
Order By: Relevance
“…In Y1 cells, the cell cycle is partially deregulated by two independent oncogenic lesions. First, constitutively high levels of K-Ras-GTP lead to the elevated activity of the phosphoinositide-3-kinase/Akt pathway (26,29,30); second, cyclins D1 and E are simultaneously induced instead of being induced sequentially (Supplementary Data, Fig. S5), meaning that progression through G 1 lies under the exclusive control of the signaling pathway: ERK1/2 !…”
Section: Discussionmentioning
confidence: 99%
“…In Y1 cells, the cell cycle is partially deregulated by two independent oncogenic lesions. First, constitutively high levels of K-Ras-GTP lead to the elevated activity of the phosphoinositide-3-kinase/Akt pathway (26,29,30); second, cyclins D1 and E are simultaneously induced instead of being induced sequentially (Supplementary Data, Fig. S5), meaning that progression through G 1 lies under the exclusive control of the signaling pathway: ERK1/2 !…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with two in vitro studies which found RhoA negatively regulated AKT phosphorylation and decreased cyclin D1 levels in endothelial cells and K-Ras-driven adrenocortical cancer cell lines. 95, 96 Another recent study of a murine colon cancer model induced by mutant APC found that simultaneous expression of dominant negative RhoA resulted in larger and more frequent adenomas and decreased survival. 97 Perhaps more intriguing, conditional gene deletion of either RhoA or RhoC alone did not suppress K-Ras G12D induced lung adenoma initiation.…”
Section: Rho Gtpases With Potential Tumor Suppressing Rolesmentioning
confidence: 99%
“…The plasmids were packaged into retroviral particles suspended in the viral vector supernatant ([10 6 c.f.u.) and used to transduce or infect HeLa cells in the presence of 4 lg/mL polybrene (Sigma) for 24 h. The selection of infected HeLa cells (clones) was performed in culture medium containing the G418 antibiotic (400 lg/mL) because the pCM vector contains the neomycin resistance gene (adapted from [19]). Six HeLa-Rac1-N17 and six HeLa-Rac1-V12 clones were isolated and tested by (a) examining Rac1 activity by measuring basal levels of Rac1-GTP in pull-down assays, (b) determining migration ability in scratch wound healing assays in the presence or absence of serum, and (c) performing clonogenic assays for checking survival (results not shown).…”
Section: Cell Culturementioning
confidence: 99%